Epidemiological Trend of Leprosy in the Post-Elimination Era at a Referral Centre in Northern Nigeria - Abu Bakar, Usman (Hind Kusht Nivaran Sangh, New Delhi, 2020)
Nigeria achieved the leprosy elimination target in the year 2000. Data demonstrating the trend of leprosy in Nigeria during the post-elimination era is limited. This study evaluates the epidemiological trend of leprosy at a referral hospital in Nigeria using leprosy control indicators. A 15-year retrospective study involving new leprosy patients registered at a referral hospital in Nigeria was conducted. Patient data were retrieved from Leprosy register and patient records. Findings shows that the new case detection rate decreased significant 5 5 from 1.6 cases per 10 in 2001 to 0.4 case per 10 by the year 2015 (regression coefficient: -0.113, 95% CI: - 0.159 – -0.067, P < 0.001); representing a 75% decline in new case detection rate. Multibacillary (MB) was the dominant type of leprosy and the proportion in new cases ranged between 74.5% and 100% during the period under review. There was also no significant change in the proportion of new cases with Grade-2-Disability (G2D), 37% in 2001 and 29.2% in 2015. The average proportion of G2D in new cases was 33.6% during the 15 year period. There was a substantial decrease in the incidence of leprosy during the period under review as reflected in the significant decline in new case detection rate. However, the high proportion of MB cases and G2D in new case underlines the need to intensify active case finding efforts as we march towards a leprosy- free-word. While the cases reporting to a referral hospital can not be use to calculate epidemiological situation at community/population level, these trends appear to be meaningful and can be used to plan studies as well as interventions at public health level.